Nurses’ Knowledge on the Prevention of Ventilator-Associated Pneumonia (VAP) among Critically Ill Patients - Alreshidi, Maha Sanat; AlRashidi, Fareda Ali; Tuppal, Cyruz P.; Al Rashidi, Nojoud; Prudencio, Denise Angelo M.; Villagracia, Rico William A.; Villagracia, Hazel N. (Nurse Media Journal of Nursing, 2024)
Background: Ventilator-associated pneumonia (VAP) is a significant concern in healthcare settings, particularly among critically ill patients who require mechanical ventilation. Nurses play a vital role in preventing VAP through their knowledge and implementation of evidence-based practices. However, there exists a notable gap in the research regarding nurses’ knowledge of preventing VAP to improve patient outcomes and reduce healthcare costs.Purpose: This study aimed to assess nurses’ knowledge of preventing VAP among critically ill patients using the ventilator bundle checklist.Methods: This study used a one-group pretest-posttest design to test the change in the nurses’ knowledge scores on VAP working in two government hospitals in Buraidah, Al Qassim Region, Saudi Arabia. The study covered 250 purposively and conveniently sampled nurses from intensive care units. Data collection was performed in three phases: pre-test, VAP educational program, and post-test. Data were collected using self-administered questionnaires on nurses’ socio-demographics, a 20-item self-made survey about the knowledge of VAP and its prevention and the adapted ventilator bundle checklist. The collected data were entered, prepared, and analyzed using SPSS version 25.0. Relevant ethical issues were strictly considered.Results: The results showed that during the pre-test, correct responses were accounted for but showed low scores in the following areas: general knowledge of VAP (27.6%), factors associated with VAP (36%), international guidelines for prevention (20.8%), and nurses’ roles in prevention (16.4%). However, in the post-test, there was a remarkable increase in the knowledge scores in the same categories (95.2%) on general knowledge, on factors associated with VAP (74.8%), on international guidelines (73.6%) and on nurses’ roles in prevention (61.6%). The program significantly improved overall VAP knowledge and knowledge in specific areas like general VAP, associated factors, international guidelines, and nurses’ roles in prevention (p<0.000).Conclusion: A pre-test revealed low baseline knowledge across all four areas assessed: general VAP knowledge, factors associated with VAP, international VAP prevention guidelines, and nurses’ roles in VAP prevention. However, post-test scores markedly increased in all areas, indicating the educational program’s effectiveness. Hence, the findings suggest that educational intervention focused on VAP screening and bundle protocols could be beneficial to address the gap in knowledge on VAP.